IN VITRO FREE RADICAL SCAVENGING ACTIVITY OF ARISTOLOCHIA TAGALA - Hadem, Khetbadei Lysinia Hynniewta; Sen, Arnab (International Journal of Current Pharmaceutical Research, 2018)
Objective: Study of antioxidant activity of a crude aqueous-methanol extract of Aristolochia tagala and its fractions and identification of the compounds with antioxidant activity. Methods: The antioxidant activity was assayed by the ability to scavenge free radicals such as superoxide, nitric oxide and ABTS radical cation and the identification of compounds was carried out by LC/MS analysis. Results: Fraction I of Aristolochia tagala showed the highest free radical scavenging activity and compounds responsible for its activity were identified as magnoflorine, apigenin dimethyl ether, aristolone, and N-trans-feruloyldopamine. Conclusion: The free radical scavenging property of the compounds present in Aristolochia tagala may be one mechanism that contributed to medicinal property exhibited by this plant.